Penambahan Dexmedetomidine Memperpanjang Lama Kerja Anestesi Blok Aksilaris - Osi; Sudjito, Hadi; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background:Dexmedetomidine is alpha 2 adrenergic receptor agonist that produces analgesia by suppressing norepinephrin secretion and blocking nerve action potential in alpha 2 receptor. This study aimed to determine if addition of dexmedetomidineof  25 µg  dexmedetomidine into 30 mL bupivacaine 0.25% shortens onset and prolongs duration of axillary block anesthesia. Methods: This phase III clinical study used double blinded randomized controlled trial design. A sample of 22 adult patients of ASA I and II were scheduled for lower arm surgery with axillary block. Patients were randomized into 2 groups. Patients in group B ( n = 11) were given 30 mL bupivacaine 0.25% and normal saline. Patients in group D (n = 11) were given 30 mL bupivacaine 0.25% and dexmedetomidine 25 µg. Results: The onset of sensory (p=0.765) and motor (p=0.748) blockade was not significantly different. But, the duration of sensory (p<0.001) and motor (p<0.001) blockade was significantly longer in group D than group B. The side effect of dexmedetomidine administration is bradycardia. Conclusion: The addition of 25 µg dexmedetomidine into 30 mL bupivacaine 0.25%does not shorten onset, but prolongs duration of sensory as well as motor blockade in axillary block anesthesia. Keywords: Dexmedetomidine, bupivacaine, axillary block, onset of sensory and motor blockade, duration of sensory and motor blockade.